Cytokine mRNA profiling of peripheral blood mononuclear cells from trypanotolerant and trypanosusceptible cattle infected with Trypanosoma congolense - O'Gorman, Grace M; Park, Stephen D E; Hill, Emmeline W; Meade, Kieran G; Mitchell, Laura C; Agaba, Morris; Gibson, John P; Hanotte, Olivier; Naessens, Jan; Kemp, Stephen J; MacHugh, David E (Physiological genomics, 2006)
To examine differences in cytokine profiles that may confer tolerance/susceptibility to bovine African trypanosomiasis, N'Dama (trypanotolerant, n = 8) and Boran (trypanosusceptible, n = 8) cattle were experimentally challenged with Trypanosoma congolense. Blood samples were collected over a 34-day period, and RNA was extracted from peripheral blood mononuclear cells. The expression levels of a panel of 14 cytokines were profiled over the time course of infection and between breeds. Messenger RNA (mRNA) transcript levels for the IL2, IL8, and IL1RN genes were significantly downregulated across the time course of infection in both breeds. There was an early increase in transcripts for genes encoding proinflammatory mediators (IFNG, IL1A, TNF, and IL12) in N'Dama by 14 days postinfection (dpi) compared with preinfection levels that was not detected in the susceptible Boran breed. By the time of peak parasitemia, a type 2 helper T cells (T(H)2)-like cytokine environment was prevalent that was particularly evident in the Boran. Increases in transcripts for the IL6 (29 and 34 dpi) and IL10 (21, 25, and 29 dpi) genes were detected that were higher in the Boran compared with N'Dama. These findings highlight the implications for using murine models to study the bovine immune response to trypanosomiasis, where in some cases cytokine expression patterns differ. Overall, these data suggest that the trypanotolerant N'Dama are more capable of responding very early in infection with proinflammatory and T(H)1 type cytokines than the trypanosusceptible Boran and may explain why N'Dama control parasitemia more efficiently than Boran during the early stages of infection.